Co-designing planning interventions to facilitate participation in mail-out bowel cancer screening - Laura E. Anderson; Larry Myers; Katelyn Collins; Jazmin Vicario; Bianca Viljoen; Michael J. Ireland; Belinda C. Goodwin (BMC, 2024)
Abstract Background Population mail-out bowel cancer screening programs save lives through prevention and early detection; however, their effectiveness is constrained by low participation rates. Many non-participants are "intenders"; that is, they intend to screen but fail to do so, often forgetting or procrastinating. This study aimed to co-design interventions to increase screening participation among intenders in the Australian National Bowel Cancer Screening Program. Methods Three semi-structured interviews, and one online cross-sectional survey, were conducted between August 2021 and December 2022. Interviews with people who had completed and returned their latest screening kit ("completers") were first conducted to identify the planning strategies they had used. Using survey data, logistic regressions were conducted to analyse strategies predictive of participants having returned their latest bowel cancer screening kit. Then, intenders were interviewed to explore their opinions of these strategies and worked with researchers to adapt these strategies into prototype interventions to facilitate screening participation. All interviews were analysed using the framework approach of codebook thematic analysis. Results Interview participants who returned their kit shared their effective planning strategies, such as putting the kit in a visible place or by the toilet, planning a time at home to complete the kit, and using reminders. Survey participants who reported using such strategies were more likely to have completed their screening kit compared to those who did not. Prototype interventions developed and endorsed by intenders included providing a prompt to place the kit or a sticker near the toilet as a reminder, a deadline for kit return, the option to sign up for reminders, and a bag to store the sample in the fridge. Conclusions These novel, consumer-led interventions that are built upon the needs and experience of screening invitees provide potential solutions to improve participation in population bowel cancer screening.